OPTIMIZATION OF CYCLE TIME IN HYUNDAI MOTORS INDIA LTD - Shrivastava, Ashish; Jain, Vaibhav; Agrawal, Tanmay; Kunwar, Siddhant (MATTER: International Journal of Science and Technology, 2016)
This paper sheds light on the application of quality control tools to reduce Cycle time (including Weld time and Squeeze time). Successive use of these tools identifies and addresses the weakness and leads to improved processes. These tools address the problems in logical and sequential manners which are easy to observe and interpret the result. The main gist of this paper is to achieve the target cycle time of body build line. Cycle time includes process time, during which a unit is acted upon to bring it closer to an output. Every production line always has a target cycle time. With the collected data it was found that cycle time was higher than the target cycle time, so it needed to be optimized. There are lots of factors which are to be eliminated in order to achieve the target cycle time. The root cause of the factors affecting the target cycle time was observed using quality improvement tools known as the Ishikawa diagram or the ‘Fish Bone Diagram’.